2015
DOI: 10.1016/j.celrep.2015.10.059
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Landscape of Renal Oncocytoma Identifies a Metabolic Barrier to Tumorigenesis

Abstract: SUMMARY Oncocytomas are predominantly benign neoplasms possessing pathogenic mitochondrial mutations and accumulation of respiration-defective mitochondria, characteristics of unknown significance. Using exome and transcriptome sequencing, we identified two main subtypes of renal oncocytoma. Type 1 is diploid with CCND1 rearrangements, whereas type 2 is aneuploid with recurrent loss of chromosome 1, X or Y, and/or 14 and 21, which may proceed to more aggressive eosinophilic chromophobe renal cell carcinoma (Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 40 publications
7
122
2
Order By: Relevance
“…A recent comprehensive analysis of the mutational landscape of human renal oncocytomas revealed that there are two main subtypes (Joshi et al, 2015). Type 1 is characterized by CCND1 rearrangements whereas Type 2 is aneuploid with loss of chromosome 1, and X or Y and/or 14 and 21, and displays male gender bias.…”
Section: Oncocytomas Accumulate Defective Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comprehensive analysis of the mutational landscape of human renal oncocytomas revealed that there are two main subtypes (Joshi et al, 2015). Type 1 is characterized by CCND1 rearrangements whereas Type 2 is aneuploid with loss of chromosome 1, and X or Y and/or 14 and 21, and displays male gender bias.…”
Section: Oncocytomas Accumulate Defective Mitochondriamentioning
confidence: 99%
“…There are few and no recurrent somatic mutations in the nuclear genome in either subtype. Type 2 oncocytoma may be a precursor of the more aggressive eosinophilic chromophobe renal cell carcinoma (ChRCC) based on similar transcriptomes and copy number variations (Joshi et al, 2015). What both renal oncocytoma subtypes share in common is recurrent pathogenic mutations in the mitochondrial genome, which may lead to ROS production that could contribute oncogenic signaling or perhaps to accumulation of oncometabolites.…”
Section: Oncocytomas Accumulate Defective Mitochondriamentioning
confidence: 99%
“…Renal cell carcinoma (RCC) consists of morphologically, molecularly, and clinically distinct subtypes, including clear cell RCC (ccRCC, ~75%), papillary RCC (pRCC, ~15%), chromophobe RCC (chRCC, ~5%), unclassified RCC (uRCC, ~5%), and few extremely rare entities such as medullary RCC (mdRCC) and MiT-translocation RCC (tRCC) (<1% each) (1)(2)(3)(4)(5)(6)(7)(8)(9). ChRCC is relatively indolent despite its usual presentation as larger tumors (10), yet ~5%-10% of patients eventually develop metastases (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that autophagy promotes metabolic robustness and malignancy through maintenance of mitochondrial function and that autophagy inhibition may suppress Kras-driven lung cancers. Interestingly, human renal oncocytomas, which typically lack Ras mutations, have pathogenic mitochondrial genome mutations, respiration defects, energy stress, and defective autophagy and may owe their benign status to similar mechanisms found in Atg7-deficient Ras-driven tumors (Joshi et al 2015).…”
Section: Lung Cancermentioning
confidence: 99%